A validated stability indicating HPTLC method for estimation of acyclovir in tablets in presence of its alkaline hydrolysis degradation product - Pallavi M. Patil; Sagar B. Wankhede; Praveen D. Chaudhari (Faculty of Pharmacy, Cairo University, 2014)
A sensitive stability indicating high-performance thin-layer chromatographic method was developed and validated for quantitative determination of Acyclovir in tablets. Chromatographic separation was performed on a precoated silica gel 60F254 HPTLC plates using Toluene: n-Butanol: Methanol: Water (5.0:3.0:1.0:1.0 v/v/v/v) as a mobile phase. A TLC scanner set at 259 nm was used for direct evaluation of the chromatograms in reflectance/absorbance mode. Acyclovir and degradant were satisfactorily resolved with Rf values of 0.62 ± 0.05, 0.78 ± 0.05, respectively. Calibration curve was a polynomial in the concentration range of 200-1000 ng/band. The high correlation coefficient (r2 > 0.9991) values indicated clear correlations between the investigated compound concentrations and their peak areas within the test ranges. The method was validated according to ICH guidelines. The repeatability and intermediate precision, expressed by the RSD, were less than 2.0%. The accuracy and validity of the method were further ascertained by performing recovery studies via a standard addition method. The accuracy of the method expressed as percent recovery was satisfactory (99.85%). The drug was subjected to the International Conference on Harmonization (ICH)-prescribed hydrolytic, oxidative, photolytic and thermal stress conditions. The method was validated according to ICH guidelines. The drug showed instability in alkaline and oxide while it remained stable in heat and UV radiation conditions. The proposed HPTLC method was utilized to investigate the alkaline degradation of Acyclovir (ACY). The performance of the method was validated according to the present ICH guidelines for specificity, limit of detection, limit of quantification, linearity, accuracy, precision, ruggedness and robustness.